Majelis Mujahidin Indonesia: Making Sense of the US Ban - Bilveer Singh (2017)
The US decision to ban the MMI in June 2017 signals a new policy towards groups allegedly linked with Al Qaeda. This is happening as the US prepares for the emergence of a post-ISIS terrorist terrain in Southeast Asia.